A mother–child intervention program for adolescent mothers: Results from a randomized controlled trial (the TeeMo study). (August 2021) - Firk, Christine; Dahmen, Brigitte; Dempfle, Astrid; Niessen, Anke; Baumann, Christin; Schwarte, Reinhild; Koslowski, Julia; Kelberlau, Kerstin; Konrad, Kerstin; Herpertz-Dahlmann, Beate
Abstract: Children of adolescent mothers are a high-risk group for negative child development. Previous findings suggest that early interventions may enhance child development by improving mother–child interaction. The purpose of the current study was to evaluate a mother–child intervention (STEEP-b) program in high-risk adolescent mother–infant dyads ( N = 56) within a randomized controlled trial (RCT). Mother–child interaction was assessed at baseline (T1), postintervention (T2), and follow-up (T3). The primary outcome was the change in maternal sensitivity and child responsiveness from T1 to T2 that was measured by blinded ratings of videotaped mother–child-interaction with the Emotional Availability Scales. A modified intention-to-treat analysis was performed to examine the data. No intervention effect was found for maternal sensitivity, 95% CI [-0.59–0.60], p = .99, and child responsiveness, 95% CI [-0.51–0.62], p = .84. Maternal sensitivity and child responsiveness did not change over time in both groups (all ps > .05). A statistically nonsignificant, but potentially clinically meaningful difference emerged between rates of serious adverse events, SC: 4 (14.8%), STEEP-b: 1 (3.4%), possibly driven by different intensity of surveillance of dyads in the treatment groups. The current findings question the effectiveness of STEEP-b for high-risk adolescent mothers and do not justify the broad implementation of this approach.